Land Weber Iterative Supervised Classification and Quantized Spiking Network for Crime Detection Emotion Analysis - M.Jayakandan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Emotion analysis is a promising tool for crime detection. It can identify potential suspects, assess the risk of violence, and track the progress of a criminal investigation. However, it cannot be easy to identify emotions accurately, and several factors can influence the results of emotional analysis. This paper proposes a new approach to emotion analysis in crime detection that utilizes Land Weber iterative supervised classification and quantized spiking network. Land Weber’s iterative supervised classification is a technique that can improve the accuracy of emotion analysis by iteratively training a classifier on a dataset of labeled data. A quantized spiking network is a type of neural network well-suited for emotion analysis because it can capture the temporal dynamics of emotions. The proposed approach was evaluated on a dataset of facial expressions and voice recordings. The results showed that the proposed approach achieved state-of-the-art accuracy in emotion analysis. The proposed approach has several advantages over traditional approaches to emotion analysis. First, it is more accurate. Second, it is more robust to noise. Third, it is more efficient. The proposed approach can improve the accuracy of emotion analysis in crime detection. It can also be used to develop new applications for emotion analysis, such as a system that automatically detect signs of deception in a witness statement. The Land-Weber iterative supervised classification algorithm has been used to detect emotions in crime detection. The quantized spiking neural network has been used to classify emotions. The study results showed that the Land-Weber iterative supervised classification algorithm achieved % overall accuracy of 97.5% in classifying emotions. In comparison, the quantized spiking neural network achieved an overall accuracy of 97.2%.